TUBERCULOSIS CONTROL - Allami, M.L (Iran University of Medical Sciences, 2003)
The resurgence of tuberculosis in recent years has made an effective control strategy in indispensable. The strategy exists and is called Directly Observed Treatment, Short-course (DOTS) which is the worldwide best and Practical approach. In a five year period since the (DOTS) was adopted by WHO as a strategy to combat tuberculosis worldwide, more than 1.2 million people have received this treatment, most of which are young and middle-aged adults, and more than 900000 of them had had the infection, smear-positive form of the disease. If these patients had only access to the conventional treatments, available in their countries, many of them would almost certainly had died and many more would have become chronic cases, spreading the disease in their communities. It is, in fact, these chronic cases remained from poor and or interrupted treatments, that become the main sources of deadly drug resistant strains of tuberculosis. Key components of the (DOTS) strategy 1. A network of trained workers able to administer, directly observed therapy at least for the first two months of the onset of the disease. 2. Laboratories equipped with trained personnel to recognize tubercle bacilli in sputum smear samples. 3. A dependable supply of high-quality drugs. 4. An accurate record-keeping and cohort analysis system for monitoring, case-finding, treatment and outcomes. 5. Sustained political commitment and funding.